Penerapan Gaussian Mixture Model pada Klasterisasi Desa di Kalimantan Barat berdasarkan Indeks Desa Membangun Tahun 2021 - Rizkia Narulita; Abdul Kudus (UNISBA Press, 2022)
Abstract. West Kalimantan is a province that actively supports the 2021 developing village index (IDM). Based on the 2021 West Kalimantan IDM data, the constituent indexes have various values and there are certain patterns. Therefore, clustering method is needed to determine groups/clusters consisting of several villages. By considering the Gaussian Mixture Model method using the expectation maximization algorithm. The purpose of this study was to determine the optimal number of clusters, and to find out the results of clustering on IDM West Kalimantan 2021 data by applying the Gaussian Mixture Model.The results of the study obtained that the optimal number of clusters was K=7, with a BIC value of 9979.939 and p-value BLRT is 0.498. Meanwhile, the results of the clustering are: (1) cluster 1 there were 436 villages with advanced social security status, very lagging economic resilience, independent environmental resilience; (2) cluster 2 there are 854 villages with advanced social security status, lagging economic resilience, developing environmental resilience; (3) cluster 3 there are 455 villages with independent social and environmental resilience status, advanced economic resilience; (4) cluster 4 contains 66 villages with independent social and economic resilience status, developing environmental resilience; (5) cluster 5 there are 106 villages with developing social and environmental resilience status, economic resilience is very lagging; (6) cluster 6 there are 64 villages with advanced social security status, lagging economic resilience, very lagging environmental resilience; (7) cluster 7 there are 50 villages with developing social security status, very lagging economic resilience, advanced environmental resilience. Abstrak. Kalimantan Barat merupakan provinsi yang aktif mendukung indeks desa membangun (IDM) 2021. Berdasarkan data IDM Kalimantan Barat 2021, indeks penyusun memiliki nilai yang beragam dan terdapat pola tertentu. Sehingga diperlukan metode klasterisasi untuk menentukan kelompok/klaster yang terdiri dari beberapa desa. Dengan pertimbangan metode Gaussian Mixture Model menggunakan penduga algoritme expectation maximization. Tujuan penelitian ini adalah untuk mengetahui jumlah klaster optimal, dan mengetahui hasil klasterisasi pada data IDM Kalimantan Barat 2021 dengan menerapkan Gaussian Mixture Model. Adapun hasil penelitian diperoleh jumlah klaster optimal K=7, dengan nilai BIC sebesar 9979,939 dan p-value BLRT sebesar 0,498. Sedangkan untuk hasil klasterisasinya, yaitu: (1) klaster 1 terdapat 436 desa dengan status ketahanan sosial maju, ketahanan ekonomi sangat tertinggal, ketahanan lingkungan mandiri; (2) klaster 2 terdapat 854 desa dengan status ketahanan sosial maju, ketahanan ekonomi tertinggal, ketahanan lingkungan berkembang; (3) klaster 3 terdapat 455 desa dengan status ketahanan sosial dan lingkungan mandiri, ketahanan ekonomi maju; (4) klaster 4 terdapat 66 desa dengan status ketahanan sosial dan ekonomi mandiri, ketahanan lingkungan berkembang; (5) klaster 5 terdapat 106 desa dengan status ketahanan sosial dan lingkungan berkembang, ketahanan ekonomi sangat tertinggal; (6) klaster 6 terdapat 64 desa dengan status ketahanan sosial maju, ketahanan ekonomi tertinggal, ketahanan lingkungan sangat tertinggal; (7) klaster 7 terdapat 50 desa dengan status ketahanan sosial berkembang, ketahanan ekonomi sangat tertinggal, ketahanan lingkungan maju.